2004
DOI: 10.1038/sj.pcan.4500707
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic effect of vitamin E and selenium in human prostate cancer cell lines

Abstract: Vitamin E and selenium are the two most popular dietary supplements used to prevent prostate cancer. The hypothesis that these antioxidants reduce prostate risk is being tested in the selenium and vitamin E chemoprevention trial (SELECT). We hypothesize that selenium potentiates vitamin E-induced inhibition of prostate cancer cell growth in vitro. Prostate cancer cell populations growing asynchronously were treated with a combination of vitamin E and selenium and processed for flow cytometric analysis. Prostat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
29
1

Year Published

2004
2004
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(30 citation statements)
references
References 12 publications
0
29
1
Order By: Relevance
“…We have previously published that vitamin E inhibits the growth of PCa cells in vitro mediated by alteration in cell cycle regulatory molecules, specifically p27 (5). In a second study, we have shown that a combination of E+S was shown to potentiate or act in synergy, thereby enhancing the proportion of cancer prevention (7). It is possible that vitamin E is effective only under certain situations and in selected model systems.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…We have previously published that vitamin E inhibits the growth of PCa cells in vitro mediated by alteration in cell cycle regulatory molecules, specifically p27 (5). In a second study, we have shown that a combination of E+S was shown to potentiate or act in synergy, thereby enhancing the proportion of cancer prevention (7). It is possible that vitamin E is effective only under certain situations and in selected model systems.…”
Section: Discussionmentioning
confidence: 91%
“…This was particularly evident with a combination of E+S+L that is in line with our previously reported in vitro synergy between micronutrients (7). This is with specific bearing to their antioxidant action and growth-inhibitory effect on PCa cells (7,14,27,28), as well as their additive effects in vitro on androgen receptor target gene expression and oxidative stress reduction in prostate tumors (29).…”
Section: Discussionmentioning
confidence: 99%
“…Our laboratory has shown that vitamin E inhibits the growth of prostate cancer cells in vitro mediated by alteration in cell cycle regulatory molecules, specifically p27 (9). A second study carried out in our laboratory revealed that a combination of antioxidants (vitamin E and selenium) is shown to potentate or act in synergy, thereby enhancing the proportion of cancer prevention (42).…”
Section: Discussionmentioning
confidence: 99%
“…The major advantage of chemoprevention compared to other forms of therapy is the lack of systemic toxicity. Another advantage is that according to recent reports chemopreventive agents, when used in combination with conventional therapies, can improve therapeutic response [2]. The relatively long latency in the development of PC makes it an appropriate target for chemoprevention at an early stage.…”
Section: Introductionmentioning
confidence: 98%